(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of the scientific and practical significance of phenological observations in botanical research. Phenology, defined as the systematic study of seasonal developmental stages in plants, is identified as a key method for understanding species biology, population ecology, phytocoenosis dynamics, and the biological impacts of climate change. The study employed a multidisciplinary approach, including field observations, laboratory analyses, statistical assessment of meteorological factors, GIS-based mapping, and remote sensing technologies.